The Effect of Corporate Social Responsibility and Good Corporate Governance on Firm Value with Financial Performance as the Mediation Variable - Meidy Ayu Nadia; Andewi Rokhmawati; Edyanus H Halim (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
The idea behind corporate social responsibility (CSR) is that companies not only have economic and legal obligation to shareholders but also obligations to stakeholders. Social responsibility (CSR) has close links with good corporate governance, like two sides of a coin; both have a strong foothold in the business world. The aim of this research was to analyze corporate social responsibility and good corporate governance to financial performance that influence the value of manufacturing companies sector basic industry and chemicals in 2015-2017, listed on the Indonesia Stock Exchange. The results of this study stated that Corporate Social Responsibility has a positive effect on financial performance, Good Corporate Governance does not affect financial performance. Corporate Social Responsibility has a positive effect on company value. Good Corporate Governance has a positive effect on company value. Financial performance has no effect on firm value. Financial performance does not mediate the relationship between Corporate Social Responsibilities to firm value. Financial performance does not mediate the relationship between Good Corporate Governance and firm value